Mechanism of chain formation under shearing forces in magneto-rheological fluids. (2021) - Chand, Mahesh; Shankar, Ajay; Pratap Singh, Avinash; Chandra Mathpal, Mohan; Prasad Pant, Rajendra; Deperyot, Jerome
Abstract: The present article focuses on the basic physics of structure formation chain formation and chain dynamics that make variation in viscoelastic properties of magnetorheological (MR) fluids. The formation and deformation of chain like structures in MR fluids at room temperature has been studied under the application of shearing force and externally applied magnetic field. The morphological investigation of MR fluid particles has been studied using SEM. A rheomicroscopy set-up was used to record the in-situ videos under magnetic field's influence and a sequence of images were taken whose analysis has been performed using ImageJ . The plot of chain length versus shear rate at constant magnetic fields reveals the competitive nature of dipole–dipole interactions and shear forces acting simultaneously.